EFEKTIVITAS PENERAPAN KEGIATAN ECOPRINT POUNDING UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA DINI DI TK MABBULO SIPEPPA KECAMATAN SIBULUE KABUPATEN BONE - Fitrya Ali Imran; A. Sri Mardiyanti Syam; NUR SYAHIDAH (Institut Agama Islam Negeri Bone, 2026)
Abstract This research aims to: 1) determine the fine motor skills of early childhood before the implementation of ecoprint pounding activities. 2) determine the fine motor skills of early childhood after the implementation of ecoprint pounding activities. 3) determine the effectiveness of the implementation of ecoprint pounding activities to improve fine motor skills in early childhood at Mabbulo Sipeppa Kindergarten, Sibulue District, Bone Regency. The type of research used in this study is quantitative research with a pre-experimental research method with a one-group pretest-posttest design carried out at Mabbulo Sipeppa Kindergarten, Sibulue District, Bone Regency with a sample of 10 children, and the approach used in this study is a pedagogical approach. Data collection techniques use observation sheet guidelines. The results of the data obtained during the study were analyzed using descriptive statistics pretest-posttest, t-test with the help of the SPSS version 26 application. The results of the study showed that: 1) children's fine motor skills before the ecoprint pounding activities were in the low category with an average value of 44.25 because there were 2 out of 10 children who had only reached the KKM of 60%. 2) The fine motor skills of early childhood after the implementation of the ecoprint pounding activity are in the increased category with an average value of 83.25 because there are 9 out of 10 children who achieved the KKM of 60%. 3) The effectiveness of the implementation of the ecoprint pounding activity has an effect on improving the fine motor skills of early childhood children obtained a value of 0.7158 with a high category. Based on the results of the t-test on the pretest and posttest, it can be seen that the 2-tailed value (significance) is 0.000 <0.05, so Ho is rejected and Hi is accepted, because the significance value obtained is 0.000 <0.05, because the significance value obtained is 0.000 so it can be said that the ecoprint pounding activity can improve fine motor skills in early childhood in group B of Mabbulo Sipeppa Kindergarten. Keywords: ecoprint pounding activity, fine motor skills, early childhood.